Quality and nutritional properties of noodles: a systematic comparison of noodles based on blue, purple, black, and white whole wheat flours - Li, Yichen; Yu, Xiaomeng; Tian, Xiaoling; Li, Mengqin; Zhang, Jian; Ma, Yan; Yin, Chenxi (Frontiers in Nutrition, 2025)
BackgroundThe increasing demand for nutritionally enriched foods has driven interest in colored wheat varieties, which may offer enhanced nutritional benefits. This study aims to compare the quality of noodles made from whole flours of blue, purple, and black wheat with a white wheat control.MethodsNoodles were formulated using different substitution levels of colored whole wheat flours, and their quality was evaluated based on nutritional properties, texture, and antioxidant capacity.ResultsThe results showed that colored whole wheat flours significantly improved the nutritional properties compared to white wheat. Black wheat exhibited the highest selenium content (5.28 μg/g), while blue wheat had the highest anthocyanin level (14.15 mg/100 g). The incorporation of colored wheat flours increased moisture content (9.15–11.36%) and cooking loss (5.22–8.34%), while reducing noodle hardness, with the 75% purple wheat substitution showing the lowest value (5347.08 g). Although processing and cooking reduced anthocyanin content and ABTS radical scavenging activity, noodles made with colored wheat retained significantly higher levels of anthocyanins (42.75–88.97%) and antioxidant capacity (16.31–47.42%) than those made with white wheat.DiscussionThese findings suggest that colored wheat varieties hold significant potential for developing functional noodles with improved nutritional profiles. Despite changes in texture, these noodles offer enhanced antioxidant activity without compromising their quality, making them a viable option for nutritionally enriched food products.